Bidirectional switchable beam splitter/filter based graphene loaded Si ring resonators. (23rd December 2021) - Bagheri, Amin; Nazari, Fakhroddin; Moravvej-Farshi, Mohammad Kazem
Abstract: Using bus waveguides coupled to the graphene-loaded Si-ring resonators (GSRRs) all on a Si-on-insulator substrate, we propose a compact bidirectional switchable beam splitter/filter controlled by graphene-based electro-absorptive (refractive) mode modulation. The design is suitable for dense wavelength division multiplexing (DWDM), according to International Telecommunication Union (ITU) standard. The proposed device consists of a through waveguide coupled to two drop waveguides via two GSRRs. Each GSRR consists of a stack of hBN/graphene/hBN nanolayers sandwiched between two Si-ring resonators. Using a finite difference time domain method, we have tuned the resonant wavelengths of GSRRs in the range of 1551.5 < λ < 1552.1 nm, linearly with the slope of ∼ 2.46 nm eV −1 via appropriately changing the graphene chemical potential, electrostatically. The numerical results show that when both GSRRs are in an electro-refractive state and a transverse electric (TE) polarized light beam of an appropriate wavelength is launched into one of the though-ports,  ∼ 84.5% of the input intensity equally splits between the adjacent drop-ports. The transmission out of the second through-port is less than 0.8%. The numerical results further show that when one GSRR is in an electro-refractive mode, and the other one is in an electro-absorptive state, ∼ 68.4% of the input intensity transmits out of the drop-port adjacent to the former GSRR, and the other ports experience insignificant outputs (<0.7%). The device's structural symmetry makes it a bidirectional tunable, suitable for long-haul optical telecommunication applications. Finally, we investigated the fabrication tolerances in the designed parameters.